2017
DOI: 10.1249/mss.0000000000001242
|View full text |Cite
|
Sign up to set email alerts
|

Muscle Metaboreflex Control of Sympathetic Activity in Obstructive Sleep Apnea

Abstract: These findings suggest an association between OSA and decreased metaboreflex control of MSNA. Muscle vasodilation during handgrip static exercise is preserved in patients with OSA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 45 publications
1
28
1
2
Order By: Relevance
“…The remarkable finding of the present study is the fact that ET decreased the levels of MSNA in individuals with moderate to severe OSA. Our results are in line with previous studies that showed that ET reduces resting MSNA in OSA ( 24 ) as well as other pathologies, including systolic heart failure ( 22 ) and myocardial infarction ( 25 ). In the present study, ET reduced MSNA (∼28.6%) towards levels lower than those observed in subjects with no OSA (∼28 bursts/min) ( 9 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The remarkable finding of the present study is the fact that ET decreased the levels of MSNA in individuals with moderate to severe OSA. Our results are in line with previous studies that showed that ET reduces resting MSNA in OSA ( 24 ) as well as other pathologies, including systolic heart failure ( 22 ) and myocardial infarction ( 25 ). In the present study, ET reduced MSNA (∼28.6%) towards levels lower than those observed in subjects with no OSA (∼28 bursts/min) ( 9 ).…”
Section: Discussionsupporting
confidence: 93%
“…MSNA was directly recorded from the peroneal nerve (leg) using microneurography (662C-4 Nerve Traffic Analysis System, The University of Iowa, Iowa City, IA, USA), according to well established methods ( 20 , 22 ). Muscle sympathetic bursts (bursts per min), and bursts per 100 heartbeats, were identified by visual inspection conducted by a single investigator, blind to the status of study participants (control vs exercise-trained).…”
Section: Methodsmentioning
confidence: 99%
“…Medium to long‐term aerobic training, at a minimum frequency of three times a week, has been shown to prevent the unwanted decline in nighttime HRV parameters in patients with moderate OSA, due to a decrease in sympathetic nerve activity (Berger et al., 2019; Kline et al., 2013; Ueno‐Pardi et al., 2017). Studies conducted in patients with OSA and heart failure have shown, through microneurography, that exercise training can decrease sympathetic nerve activity following a 4‐month training program, at a frequency of three times a week (Ueno‐Pardi et al., 2017). Recently, it has been also shown that regular aerobic exercise is capable of increasing parasympathetic tone in OSA patients already by the 12th week of intervention (Yang et al., 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Repeated events of hypoxia and reoxygenation lead to an increase of reactive oxygen species (2), insulin resistance (3), systemic inflammation, vascular dysfunction, and increase in sympathetic nervous activity (4), placing OSA patients at risk for cardiovascular disorders and neuropsychological symptoms that include mood changes (5). These changes in patients with OSA lead to impaired daytime performance (6) and increased occupational and motor vehicle accidents (7), which translate into difficulties in social adjustment related to fatigue (8,9).…”
Section: Introductionmentioning
confidence: 99%